Implementation of Operating Wound Care Intervention in Post-Laparatomy Sectio Caesarean Patients at Rsud X - Dina Puspita Hariyanto; Shindi Hapsari (Jurnal EduHealth, 2026)
Sectio Caesarea (SC) is a surgical procedure that carries the risk of causing post-operative complications such as acute pain, impaired skin and tissue integrity, and surgical wound infection, so that appropriate and comprehensive wound care is needed to accelerate the healing process and improve patient comfort. This Final Scientific Paper for Nurses uses a case study design with a nursing process approach in five post-operative laparotomy sectio caesarea patients treated in the Bougenville (Postpartum) Room of RSUD X, with data collection through interviews, observations, physical examinations, and wound observations using the REEDAN approach. The results of the study indicate that the main nursing problems are impaired skin and tissue integrity and acute pain, and after the implementation of wound care interventions that include monitoring wound characteristics, applying sterile techniques, infection prevention, pain management, self-care wound education, and collaboration with medical therapy, the condition of the wound has improved as indicated by clean and dry wounds, no signs of infection, and decreased pain intensity. It can be concluded that the implementation of surgical wound care interventions comprehensively and according to nursing care standards is effective in accelerating wound healing and improving the comfort of post-sectio caesarea patients .